Removing impulse noise images by using decision tree algorithm - Sethu, Devika; Hasoon, Feras N.; Hasson, Nebras N.; Al-Assadi, Hayder M. A. Ali (2007)
Presently, a digital image is obtained through a suitable digital imaging system. Although the current technology has tremendously advanced, no imaging system is perfect in generating images that are identical to their originals because of the inherent physical limitations. During the filtering of noisy image, important features such as edges, lines and other fine image details embedded in the image tends to blur because of filtering operation. The enhancement of noisy data, however, is a very critical process because the sharpening operation can significantly increase the noise. In this proposed approach we aim to develop image processing technique that can meet this new requirement, which are high quality and high speed. Furthermore, prevent the noise accretion during the sharpening of the image details, and compare the restored images via proposed method with other kinds of filters.